Blood Glucose Level Estimation Using Interdigital Electrodes - Pockevicius, V.; Markevicius, V.; Cepenas, M.; Andriukaitis, D.; Navikas, D. (Elektronika ir Elektrotechnika, 2013)
In this article we are investigating whether it is possible to determine non-invasive glucose concentration in blood. With software "Comsol Multiphysics 4.3a" we are simulated environment similar to the human body and choose the most suitable interdigital electrodes. With them we are carry out investigations and measure concentration of glucose in the blood. With this method, the human body will not be injured and not infected with infection it will be psychologically harmless to. DOI: http://dx.doi.org/10.5755/j01.eee.19.6.4566